Ketahanan Papan Partikel Terhadap Suhu Tinggi, Serapan Air dan Perilaku Patah - Dian Sestining Ayu; Edi Kurniadi (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
Wood is widely used for structural and non-structural purposes. In non-structural purpose, wood is used, among others, as furniture, parquet (wood floor), partitions and so on. In line with the decreasing availability of wood, the price of wood is becoming increasingly expensive. In certain uses, substitute materials such as particle boards have been started to use. Particle boards are generally composed of certain wood powder wastes. This study aimed to look for alternative materials for building particle boards from coconut shells. The particle boards to be tested were composed of coconut shells with the addition of certain wood powder which is added with certain percentage. Particle boards were printed with a certain size, given certain pressure and tested for their physical properties. The physical properties of the particle boards tested included particle density, water absorption, dry flexural modulus, and dry bending fracture modulus. The results showed that the best mixture composition capable of producing density values, water absorption, fracture modulus and optimum modulus of elasticity were found in the proportion of mixtures of 70-90% coconut shell particles and 30-10% wood particles.